Oxidative stress in amyotrophic lateral sclerosis (ALS) 2 - Shaw, Pamela (Henry Stewart Talks, 2022)
Evidence for oxidative stress in other subtypes of Motor Neuron Disease (MND), Causes of oxidative stress in MND, The role of TDP-43 in MND, Eleven main pathophysiological mechanisms in ALS/MND, Oxidative stress as a therapeutic target in MND, Ebselen, Riluzole, Edaravone, copper ATSM, and Dimethyl fumarate trials